Flight capacity drives circadian patterns of metabolic rate and alters resource dynamics. Issue 6 (19th April 2022) - Stahlschmidt, Zachary R.
Abstract: Animals must acquire, use, and allocate resources, and this balancing act may be influenced by the circadian clock and life‐history strategy. Field ( Gryllus ) crickets exhibit two distinct life‐history strategies during early adulthood—flight‐capable females invest in flight muscle at a cost to ovary mass, whereas flight‐incapable females instead invest solely into ovaries. In female Gryllus lineaticeps, I investigated the role of life‐history strategy in resource (food) acquisition and allocation, and in circadian patterns of energy use. Flight capacity increased the standard metabolic rate (SMR) due to greater late‐day SMR and flight‐capable crickets exhibited greater circadian rhythmicity in SMR. Flight‐capable crickets also ate less food and were less efficient at converting ingested food into body or ovary mass. Thus, investment into flight capacity reduced fecundity and the amount of resources available for allocation to other life‐history traits. Given the increasing uncertainty of food availability in many global regions, work in Gryllus may clarify the important roles of food and circadian patterns in life‐history evolution in a changing world. Abstract : Wing‐dimorphic crickets offer unique insight into the costs and benefits of flight capacity. Here I show that flight capacity increases the circadian rhythmicity of metabolic rate, and I further show that flight‐capable crickets eat less food and are less efficient at converting ingested food into body or ovary mass. In sum, investment into flight capacity in a field cricket can represent a risky energetic strategy that reduces fecundity and the amount of resources available for allocation to other life‐history traits. Research Highlights: In a field cricket, investment into flight capacity (1) increased the circadian rhythmicity of resource use (standard metabolic rate), (2) reduced resource acquisition (food intake), and (3) reduced the efficiency by which ingested food was converted to reproductive tissue.